Hypo and Antihyperglycaemic Effect of Citrullus colocinthis L. Seeds in Normal and Streptozotocin-Induced Diabetic Rats - BENMEHDI, H.; ALLALI, H.; TABTI, B.; DJABOU, N.; BENDIABDELLAH, A.; LAHFA, F.; DJAZIRI, R. (Asian Journal of Chemistry, 2010)
Citrullus colocinthis L. is used in Algerian folk medecine for the treatment of diabetes mellitus. Intra peritoneal administration of the aqueous extract of the seed (1.25 g/kg body weight) to streptozotocin-induced diabetic rats produced a significant reduction of blood sugar level in the long term, while the same extract produced no alteration of glycaemia in normal rats in the short term. The aqueous extract of this plant seems to have maximal adverse effect and high LD100 value.